Profitability and Liquidity Analysis of Capital Structure in Mining Companies - Arianto Taliding; Monalisa; Meldilianus N.J.Lenas; Fausiah; Aminah (Universitas Muhammadiyah Palu, 2023)
This study aims to analyze the profitability and liquidity of the capital structure of mining companies listed on the Indonesia Stock Exchange in 2018-2020. The sample in this study is a mining company listed on the Indonesia Stock Exchange with complete financial reports for 2018-2020. The data in this study was collected by documentation obtained through www.idx.co.id. The results of the survey will be analyzed using multiple regression analysis. This study's results show that profitability, as measured using Return on Equity (ROE) and Return on Asset (ROA), partially influences the capital structure. However, liquidity measured using Current Ratio (CR) and Quick Ratio (QR) partly does not affect the capital structure.